The Meanings of Signs in Victoria’s Secret Advertisement - I Gusti Komang Oka Wardayuna; I Nengah Sudipa; Putu Ayu Asty Senja Pratiwi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study is entitled The Meaning of Signs in Victoria’s Secret Advertisement. This study focuses on the analysis of verbal and visual signs in the poster available on the Victoria’s Secret website. It aims to identify the kind of signs implied in Victoria’s Secret advertisements and to analyze the meaning of the signs implied in Victoria’s Secret advertisements. This study used advertisements as primary data. This study applied the documentation method and note-taking technique in collecting data. This study used qualitative methods and the data was analyzed descriptively. The result of this study was presented in the informal method. Three theories were applied in this study. Dyer's (1982) theory was used to analyze the signs, particularly the verbal and visual signs found in the data. Then, the verbal signs meaning was analyzed through the theory from Barthes (1964) on the meanings of the signs and the color theory by Cerrato (2012) to analyze the meaning of the color in the data. The result shows that there are eight signs found in the data, four of them are categorized as verbal signs, and four others are visual signs. The verbal signs are visible through the placement, shape, and color of the texts, meanwhile, the visual sign focuses on the situation that happens throughout the posters. Based on the analysis, one verbal sign has a denotative meaning, another has a denotative and connotative meaning, and one does not have a denotative and connotative meaning, however, none of the data shows any myth aspects. Then, there is no dominant color found in the data because the colors in the data are different from one another.